PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN BAHASA INDONESIA MATERI KOSAKATA KELAS IV SD NEGERI NAPUNGLANGIR - Paula Emerentiana; Veronika Jeo; Lukas Bera (STKIP Subang, 2026)
The issue addressed in this study is that students' vocabulary mastery remains low; they struggle to comprehend word meanings, synonyms, antonyms, and word usage within sentences. Furthermore, instruction has not sufficiently incorporated activities that actively involve students, thereby limiting opportunities for interaction, discussion, and the identification of word pairs—factors that ultimately impact student learning outcomes. This study aimed to determine the effect of the